Taxonomic study of the leafhopper genus Raabeina Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini), with description of a new species from China - Lin, Shuanghu; Zhang, Yalin (Zootaxa, 2019)
The genus Raabeina Dworakowska is reviewed, including one new species R. longhiensis sp. nov. from Guangxi Province, China. Detailed morphological description and illustration of this new species is provided. A key to all known species (males) is given.